Assessment of the different skin sensitization potentials of irritants and allergens as single substances and in combination using the KeratinoSens assay. (7th February 2021) - De Rentiis, Anna M. A.; Pink, Mario; Verma, Nisha; Schmitz‐Spanke, Simone
Abstract: Background: People are exposed to mixtures containing allergens and irritants often causing contact dermatitis. Therefore, regulatory authorities require systematic information on the effects of mixtures on the sensitization threshold. In this study a moderate (cinnamal) and a weak (ethylene glycol dimethacrylate) allergen were combined with irritants covering different mechanisms of action (sodium dodecyl sulfate, salicylic acid, and α‐pinene). For a systematic approach, the single substances were initially tested using the KeratinoSens assay. Thereafter, each allergen was combined with noncytotoxic concentrations of the irritants. Method: The KeratinoSens assay was applied for the single substances according to OECD (Organisation for Economic Co‐operation and Development) Test Guideline 442D. Based on these results, three noncytotoxic concentrations of the irritants were selected and applied simultaneously with 12 concentrations of the allergens to the KeratinoSens cells. Sensitization threshold and cytotoxicity were measured and compared with the individual testing. Results: The combinations of allergens and irritants differed from the effects of the single substances and lowered the sensitization threshold. The quantitative approach allowed a clear description of the changes which varied by factors between 1.1 and 10.3. Conclusions: Overall, the allergen was the prominent compound in the mixture and its nature appeared to determine the degree of the response. Highlights: Mixtures containing one irritant and one allergen induced additive and synergistic responses in the KeratinoSens assay compared with the allergen alone. Strength of the response mainly depended on the chosen allergen.